Storybook Literacy Method Increasing Language Development in Children with Speech Delay - Darah Ifalahma; Agostinha Morais Assis Belo; Avelino Gomes dos Santos; Liss Dyah Dewi Arini; Tirla Puspita Dewi (Global Health Science Group, 2022)
Children's speaking ability is very important in their development. Stages in a child's language development sometimes experience delays and can become a nuisance. The most common and easily recognizable language disorder is speech delay, which means the child's level of speech development is not appropriate for his age. One of the actions that can be taken for children who have speech delays is the storybook literacy method. This method can help develop and train children's language skills and through stories children are required to be active in developing language. The purpose of the study was to determine the effectiveness of the storybook literacy method on language development in children with speech delay. This study uses the One Group pre-test and post-test design. Sampling technique using non-probability sampling saturated sampling type. The sample is 10 children with mild speech delay. The research instrument was using the Stimulation of Early Intervention Detection of Growth and Development (SDIDTK) instrument through the KPSP form. The analysis used is the T-Test. The results of the T-Test test obtained a p-value of 0.000, which means that there is an influence of the storybook literacy method on children's language development with speech delay. Storybook literacy method is effective to improve language development in children with speech delay.